Enhanced tumor cell killing by ultrasound after microtubule depolymerization. Issue 3 (11th June 2021) - Singh, Aditi; Tijore, Ajay; Margadant, Felix; Simpson, Chloe; Chitkara, Deepak; Low, Boon Chuan; Sheetz, Michael
Abstract: Recent studies show that tumor cells are vulnerable to mechanical stresses and undergo calcium‐dependent apoptosis (mechanoptosis) with mechanical perturbation by low‐frequency ultrasound alone. To determine if tumor cells are particularly sensitive to mechanical stress in certain phases of the cell cycle, inhibitors of the cell‐cycle phases are tested for effects on mechanoptosis. Most inhibitors show no significant effect, but inhibitors of mitosis that cause microtubule depolymerization increase the mechanoptosis. Surprisingly, ultrasound treatment also disrupts microtubules independent of inhibitors in tumor cells but not in normal cells. Ultrasound causes calcium entry through mechanosensitive Piezo1 channels that disrupts microtubules via calpain protease activation. Myosin IIA contractility is required for ultrasound‐mediated mechanoptosis and microtubule disruption enhances myosin IIA contractility through activation of GEF‐H1 and RhoA pathway. Further, ultrasound promotes contractility‐dependent Piezo1 expression and localization to the peripheral adhesions where activated Piezo1 allows calcium entry to continue feedback loop. Thus, the synergistic action of ultrasound and nanomolar concentrations of microtubule depolymerizing agents can enhance tumor therapies.